Space, Place and Educational Settings - Freytag, Tim; Lauen, Douglas L.; Robertson, Susan L. (Knowledge and Space, 2022)
This open access book explores the nexus between knowledge and space with a particular emphasis on the role of educational settings that are, both, shaping and being reshaped by socio-economic and political processes. It gives insight into the complex interplay of educational inequalities and practices of educational governance in the neighborhood and at larger geographical scales. The book adopts quantitative and qualitative methodologies and explores a wide range of theoretical perspectives by drawing upon empirical cases and examples from France, Germany, Italy, the UK and North America, and presents and reflects ongoing research of international scholars from various disciplinary backgrounds such as education, human geography, public policy, sociology, and urban and regional planning. As such, it provides an interesting read for scholars, students and professionals in the broader field of social, cultural and educational studies, as well as policy makers and practitioners in the fields of education, pedagogy, social work, and urban and regional planning.